Studying the effect of full uniform shading on a PV module using a LabVIEW simulation model - Hertzog, Pierre E; Swart, Arthur J (Stellenbosch: Southern African Universities Power Engineering Conference SAUPEC, 2017)
Simulations designed in LabVIEW may be used in many engineering applications, including the design of stand-alone PV systems. The influence of full uniform shading, which included thin clouds and contrails, on the day to day performance of PV systems is often underestimated, and is not always accounted for in the design. The purpose of this paper is to describe the design and development of a LabVIEW simulation model that includes the influence of full uniform shading on the overall performance of a PV system. This model is used by electrical engineering students at the Central University of Technology in order to verify their designs and improve their understanding of the operation of stand-alone PV systems. The model also assists engineering students in investigating the influence of full uniform shading on the performance and sustainability of a stand-alone PV system with specific component specifications. The design of the model was based on empirical research that quantified the influence of full uniform shading on the performance of a PV system. With the use of this model, a engineering student can change the percentage of full uniform shading in conjunction with other variables, thereby visually observing the influence on the performance of a stand-alone PV system over a 24-hour period.
Conference Proceedings
Keywords: PV design; sustainability; diffuse radiation; engineering students